A New Method for Isomorphism Identification of Planetary Gear Train based on Improved Hamming Number - Sun Wei; Li Anming; Kong Jianyi; Zuo Huiyan; Wei Sijia (Jixie chuandong)
The isomorphism identification is one of the indispensable processes in structure synthesis of planetary gear train.It is of great significance for the creation of novel planetary gear train with excellent transmission characteristics.A new method for identifying isomorphism of planetary gear train based on improved Hamming number is proposed.Firstly，a new method for describing the topological diagram of planetary gear train by improved link adjacency matrix is proposed.This matrix contains all the information of the topological structure of planetary gear train and has the uniqueness of description.Then，the basic feature of planetary gear train is represented by the feature code，which is the necessary condition for isomorphism.Then，the principle of improved Hamming number is defined，and the Hamming code is obtained.By distinguishing whether the structural constants of the feature code and the Hamming code are equal，the isomorphism of the planetary gear train is identified.Finally，the validity and reliability of the method are verified by examples.